Essentials of EU law - Reinisch, August 1965- (Cambridge University Press, 2012)
Students new to the study of EU law can find knowing what questions to ask to be as much of a challenge as answering them. This book clearly sets the scene: it explores the history and institutions of the EU, examines the interplay of its main bodies in its legislative process and illustrates the role played by the EU Courts and the importance of fundamental rights. The student is also introduced to the key principles of the internal market, in particular the free movement of goods and the free movement of workers. In addition a number of other EU policies, such as the Common Agricultural Policy, Environmental Protection and Social Policy are outlined, while a more detailed inquiry is made into European competition law. This book is an essential first port-of-call for all students of European law
Title from publisher's bibliographic system (viewed on 08 Oct 2015)
Keywords: Europäische Union; European Union / History; Geschichte; Recht; Law / European Union countries; Law / European Union countries / Miscellanea; Europäische Union. Mitgliedsstaaten; Einführung